The Implementation of the Independent Learning Curriculum in Indonesian Language Instruction to Foster Student Creativity - Riska Maulita Hasibuan; Ade Kusmana; Rustam Rustam (EDUTEC : Journal of Education And Technology, 2024)
This study aims to examine, describe, and analyze the implementation of the "Merdeka Curriculum" in Indonesian language instruction to foster the creativity of students at SMK Baiturrahim, Jambi City. Additionally, it aims to assess the impact of this curriculum on developing students' creativity. The study employs a qualitative descriptive research method. This approach was chosen to provide a detailed description of how the "Merdeka Curriculum" is applied in Indonesian language learning to enhance the creativity of students at SMK Baiturrahim. The findings indicate that the curriculum has been successfully implemented in Indonesian language learning. The adoption of the "Merdeka Curriculum" has led to a positive transformation in student creativity. This is evidenced by the emergence of four key concepts of creativity in students: critical thinking, emotional sensitivity, the development of personal skills and talents, and strong imagination. The curriculum has been effectively implemented at SMK Baiturrahim, facilitating critical and rational thinking, emotional sensitivity, the discovery of students' personal skills and talents, and encouraging strong imagination. Furthermore, the impact of the curriculum enables students to explore their skills and talents during the learning process, leading to inventive and original learning outcomes.